2007
DOI: 10.1111/j.1741-3737.2007.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Support Between Siblings and Between Friends: Two Worlds Apart?

Abstract: This research examines whether siblings and friends resemble each other in supportive behavior. Using a Dutch national sample of 6,289 individuals containing 12,578 relationships with siblings and friends, we investigated the relative importance of gender composition, geographical proximity, relationship quality, and contact frequency for support exchange with siblings and friends. Results show that, controlling for other influences, siblings exchange more practical and less emotional support. High relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 33 publications
3
37
1
14
Order By: Relevance
“…Our results support the view of gratitude as a prosocial emotion that serves to trigger and maintain reciprocal interactions in friendships (Algoe et al, 2008;Trivers, 1971). Although the effect sizes for gratitude by relationship type were not large, this is in line with previous studies that have found relatively small but persistent differences between friends and kin in help scenarios (Stewart-Williams, 2007;Voorpostel and van der Lippe, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results support the view of gratitude as a prosocial emotion that serves to trigger and maintain reciprocal interactions in friendships (Algoe et al, 2008;Trivers, 1971). Although the effect sizes for gratitude by relationship type were not large, this is in line with previous studies that have found relatively small but persistent differences between friends and kin in help scenarios (Stewart-Williams, 2007;Voorpostel and van der Lippe, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…-682-result: The effect of contact frequency on the provision and reception of emotional support was stronger among siblings compared to friends (Voorpostel and van der Lippe, 2007). This pattern may stem from a selection effect.…”
Section: Discussionmentioning
confidence: 69%
“…Longitudinal studies reveal that these behaviors decline across adolescence as youth focus on the world beyond the home (Kim, McHale, Osgood, & Crouter, 2006). Positivity in sibling relationships, however, continues to be linked to more positive psychological adjustment into young adulthood and beyond (Voorpostel & van der Lippe, 2007). Sibling conflict behaviors include verbal (tease, argue), relational (social exclusion, undermining) and physical aggression (Dunn, 2007).…”
Section: Theoretical Perspectives On Sibling Relationship Behaviorsmentioning
confidence: 99%
“…According to the “compensation model,” deficiencies in support from close familial relationships, such as parents and siblings, can be compensated by support obtained from relationships outside the family, such as friends or peers (East and Rook 1992; Gauze et al 1996; Magdol and Bessel 2003; Sherman et al 2006; Voorpostel and van der Lippe 2007; see also Wellman and Wortley 1990). This work is interested in the impact of substitution on individuals’ psychological adjustment—paralleling the migrant adaptation literature—which may explain its emphasis on replacement of psychosocial support of the family, including elements such as companionship, affection, trust, and emotional encouragement.…”
Section: Theoretical Frameworkmentioning
confidence: 99%